Pengembangan Video Pembelajaran PKn Model Contextual Teaching Learning di Kelas IV SD Negeri 3 Sembawa - Arisandi, Indi; Hakim, Lukman; Prasrihamni, Mega (Indonesian Research Journal on Education, 2022)
The purpose of development research is to produce Civic Education learning videos with a valid, practical, and effective CTL model. This research uses research and development type. The development model in this study refers to the 4D (four-D) research and development model. The4D research and development model consists of 4 main stages, namely define, design, develop,and disseminate. Characteristics of learning videos made using simple and easy to understandlanguage. The learning video that was developed to increase students' interest in learning was inthe appropriate category with the predicate of the assessment results of design feasibility 3.50,linguistic feasibility 3.75, material feasibility 3.90 and an average value of 3.71. the calculation ofthe pretest and posttest students' interest in learning got a final score of 85.74. and the teacher's response questionnaire was 3.8. For teachers, they should start to innovate using learning video media that they made themselves, for schools should facilitate teachers and students to be able to create and use learning video media, and for advanced researchers should perfect research that will be carried out further based on references from research that has been done.